Fortuitous diagnosis of “full stomach” made by using ultrasonographic examination of the antrum in two elective patients - Lionel Bouvet; Caroline Augris; Clémence Aubergy; Dominique Chassard (Journal of Ultrasonography, 2016)
We report two cases of patients presenting for elective surgery, in whom significant gastric contents were identified by performing fortuitous ultrasound examination of their antral area. The first patient presented for a day-case surgery scheduled under regional anesthesia. With his consent, ultrasound examination of the antral area was by chance performed within the context of training for this technique, showing significant solid contents in the stomach. The patient admitted that he had not respected preoperative fasting. The second patient was scheduled for an elective ophthalmologic surgery. Ultrasound examination of the antrum showed that the antrum was dilated, with significant solid and liquid gastric contents. This case may be related to a strongly delayed gastric emptying. These two cases demonstrate that some elective patients may present with significant gastric contents exposing them to the risk of pulmonary aspiration in the case of general anesthesia.